Transition from oceanic subduction to continental collision in central Tibet: evidence from the Cretaceous magmatism in Qiangtang block. Issue 4 (21st February 2022) - He, Haiyang; Li, Yalin; Ning, Zijie; Wang, Chengshan; Xiao, Siqi; Bi, Wenjun; Zhang, Huanbao; Wang, Zhengqing; Chen, Liang
ABSTRACT: The Mid-Late Mesozoic magmatic arc in southern Qiangtang block was associated with the long-lasting subduction of the Bangong-Nujiang Tethyan and the subsequent Lhasa-Qiangtang collision. The detailed processes associated with the transition from oceanic lithosphere subduction to lithosphere delamination remain unclear. This paper reports zircon U-Pb age, major and trace element and Sr-Nd isotopic data for the Cretaceous two-phase magmatic rocks in the Shuanghu region of the southern Qiangtang block located in central Tibet. Zircon dating on the Qushenla volcanic rocks yields a 206 Pb/ 238 U age of 114 ± 4 Ma. The Abushan volcanic rocks comprise rhyolites. Zircon dating on two rhyolites yields a 206 Pb/ 238 U age of 74 ± 1 to 76 ± 1 Ma. In contrast with the Qushenla volcanic rocks, the Abushan rhyolites exhibit features typical of high-fractionated I-type granitoids, high K calc-alkaline and shoshonite, and peraluminous, suggesting that the Abushan rhyolites formed in post-collision setting. The Qushenla volcanic rocks have slightly higher initial 87 Sr/ 86 Sr (0.70466–0.70537), and εNd(t) (1.71–2.89) in comparison with the Abushan rhyolites ( 87 Sr/ 86 Sr = 0.70453–0.70491, εNd(t) = 1.63–2.35). The Qushenla volcanic rocks were most likely derived from the mixing of mantle-derived components and crustal material. And the crust assimilation and fractional crystallization played a role during the ascent of magma. The Abushan volcanic rocks derived from magmatic mixing between the crustal materials and mantle-derived components, and undergoing extensive fractional crystallization. Taking into account the regional tectonic and magmatic data, we suggest that the transition from the oceanic lithosphere subduction to lithosphere delamination occurred during the Late Cretaceous in central Tibet. It evolved through three stages: 125–100 Ma, late subduction of Bangong-Nujiang Tethys; 100–87 Ma slab break-off of subduction Bangong-Nujiang Tethys; and 87–73 Ma lithosphere delamination.